Characterizing the Strength of Evidence in FDA Labels for Pharmacogenomic Biomarker-Guided Medication Use - Chin, Lauren (AMIA Jt Summits Transl Sci Proc, 2017)
There is great heterogeneity in drug treatment response that is thought to be due to individual-level allelic variation in pharmacogenomic biomarkers. FDA Drug Labels provide information to guide pharmacogenomic biomarker use. Yet, the strength of evidence for clinical validity and clinical utility is lacking. We characterized the strength of evidence and treatment recommendations contained in FDA Drug Labels as of December 2015. Pharmacogenomic biomarker information was provided for 137 drugs, involving 49 pharmacogenomic biomarkers, constituting 166 drug-biomarker pairs. Convincing/adequate evidence of clinical validity was found for 46% of pairs, of clinical utility for 29% of pairs, and of both, for 27% of pairs. Despite evidence of convincing/adequate validity/utility, no treatment recommendation was provided for 37% of pairs. Germline biomarkers represented nearly three-quarters of all drug-biomarker pairs, however, only 29% and 16% of pairs had convincing/adequate evidence for clinical validity and clinical utility, respectively. Separately, somatic biomarkers that serve as molecular targets for targeted therapies, had convincing/adequate evidence for 95% of pairs for clinical validity, and for 67% for clinical utility. The strength of evidence for pharmacogenomic biomarker use is low, underscoring the need for additional research to achieve the promise of precision medicine.